PENERAPAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE SESUAI DENGAN PERATURAN DAERAH KABUPATEN BANYUWANGI NOMOR 9 TAHUN 2013 - Fitri, Icha Cahyaning; Zuhroh, Siti Fatimatul (Universitas Muhammadiyah Jember, 2021)
Garbage is the residue of human business or activities in solid form, either in the form of organic or inorganic substances that are biodegradable or non-biodegradable and are considered no longer useful so that they are disposed of into the environment. The phenomenon of the distribution of waste in Indonesia is currently rampant, due to the lack of public awareness to dispose of waste in the places provided. This causes the amount of waste to increase every year. In addition, the distribution of waste is caused by the absence of legal firmness regarding waste policies, the lack of waste management efforts, uneven means of transporting waste, the inadequate Final Disposal Site (TPA) system and the lack of public awareness in reducing the volume of waste. The waste management is regulated in Article 19 of Law Number 18 of 2008 concerning Waste Management which is carried out by handling and reducing waste. In addition, there is also a principle to regulate the increasingly rampant distribution of waste, namely the principle of good environmental governance. This principle in a regional regulation will produce a permanent legal force that is coercive. It is intended to preserve the environment through environmentally sound waste management.